HUBUNGAN TINGKAT PENGETAHUAN PERILAKU PERSONAL HYGINE GENITAL DAN PENCEGAHAN TERHADAP KEJADIAN KEPUTIHAN PATOLOGIS PADA SISWI SMA NEGERI 1 PERBAUNGAN - KIKI NUR UTAMI; ANNISA . (LP2MTBM MAKARIOZ, 2021)
Leucorrhoea is a clinical disorder that is often complained of by all women, especially in young women who have just enteredpuberty. Leucorrhoea is both pathological and physiological. Physiological leucorrhoea is whitish that arises as a result ofnatural processes in the body, while pathological leucorrhoea is whitish that arises due to fungal, bacterial and viralinfections. About 75% of Indonesian women have experienced vaginal discharge at least once in their life and 45% of themhave experienced vaginal discharge twice or more. To determine the relationship between the level of knowledge, personalgenital hygine behavior, and the prevention of pathological vaginal discharge in high school students of 1 Perbaungan. Theresearch method used was analytic observational with a cross sectional approach. This research was conducted at SMAN 1Perbaungan with a total sample of 85 people. The statistical analysis of this study showed that there was a significantrelationship between the level of knowledge (p = 0.000) personal hygiene genital behavior (p = 0.000) and prevention (p =0.000) with the incidence of pathological vaginal discharge in SMA Negeri 1 Perbaungan students. There is a significantrelationship between the level of knowledge, personal hygiene genital behavior and prevention with the incidence ofpathological vaginal discharge in SMA Negeri 1 Perbaungan students.